Investigation of Middle School Students’ Solution Strategies in Solving Proportional and Non-proportional Problems - Mutlu Pişkin Tunç (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The purpose of this study was to investigate middle school students’ solution strategies in solving different types of proportional (i.e., missing value, numerical comparison and qualitative reasoning problems) and non-proportional problems and to compare if differences existed between sixth and eighth grades students’ solution strategies. Data were collected from 101 sixth grade (n=44) and eighth grade (n=57) students from three different public middle schools. The students were asked to solve ten open-ended items that included seven proportional problems and three non-proportional problems. Descriptive data analysis methods were used to analyze data. The results revealed that the students’ solution strategies differed based on problem type and grade level. The eighth grade students used cross-multiplication as a leading strategy whereas the sixth grade students used factor of change strategy. Moreover, the results showed that students commonly used incorrect proportional strategies to solve non-proportional problems.